Conception rate following intra-cervical artificial insemination using frozen semen at field level in indigenous sheep of Bangladesh - Mansur, Md Abdullah Al; Alam, Md Golam Shahi; Jha, Pankaj Kumar; Rimon, Md Asaduzzaman; Naher, Nazmun; Bari, Farida Yeasmin (Asian Journal of Medical and Biological Research, 2018)
This study was undertaken to study the AI conception rate using frozen semen at field level. Five farms in Mymensingh, Bangladesh were selected for AI Trial in field ewes. Four rams were selected for semen collection, evaluation, and frozen semen production and further to study conception rate followed by intra-cervical AI in both natural and synchronized ewes. Conception rate were confirmed by non-returned rate and ultrasound scanning at 30-40 days of post insemination. The volume, colour, mass activity, sperm motility, viability, concentration, HOST +ve (%) and normal spermatozoa percentages were 0.8±0.3 ml, 3.9±0.3, 4.4±0.6, 81.3±5.0%, 90.0±4.0%, 3519.0±545.6x106/ml, 87.4±3.3% and 85.6±1.8%, respectively. The sperm concentration of ram R#6 was significantly higher (P<0.05) (4120.5±93.5x106/ml) compared with other rams. The mean motility and viability of pre-dilution, 120 minutes of addition of Part-A, 240 minutes of addition of Part-B and post-thaw were (83.8±4.8%, 81.3±2.5%, 80.0±4.1% and 41.3±9.5%) and (93.3±1.0%, 90.0±1.4%, 88.8±1.0% and 58.3±8.7%), respectively. There were no significant difference (P˃0.05) between pre-dilution and post-dilution sperm motility and viability percentage however, post-thaw sperm motility and viability significantly (P<0.05) decreased compare with the motility and viability of pre-dilution and post-dilution values. Motility and viability percentages of frozen semen did not decrease significantly (P> 0.05) with the increase of preservation time. The mean motility and viability at 24 hrs, day 7, day 15 and day 30 were 41.3±9.5%, 41.5±8.5%, 41.8±9.9% and 40.5±10.2%; and 59.0±10.1%, 58.5±7.7%, 59.0±8.8% and 57.8±8.3%, respectively. The conception rates in natural and synchronized estrous were 26.7% and 25%, respectively. There was no significant difference in conception rates between the natural and synchronized oestrous in field level. However, the present non-return rate and conception rate indicate the suitability of produced frozen semen application in the field level. Asian J. Med. Biol. Res. March 2018, 4(1): 55-62